Analisis Pembangunan Dalam Pengembangan Wilayah Provinsi Banten - Bajuri, M.Haikal Kamil; Maulana, Feri; Asrilah, Dina; Alqorni, Tholib (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses the importance of the regional approach in reducing development disparities across various regions. In the context of regional development in Banten Province, the development strategy focuses on spatial planning, infrastructure, settlements, and sustainable economic growth. Through a literature review, this article identifies regional development theories, the morphological profile of the Banten region, population density by regency/city, as well as regional development strategies in Banten. The discussion covers development theories, the general overview of the Banten region, population density, equitable distribution and regional development, as well as forms of regional development within the development strategy. The research method used in this article is a literature review, which involves the collection, analysis, and synthesis of information from various written sources relevant to the topic of regional development in Banten Province. Through the literature review, the authors examine and summarize the findings from previous research, books, scientific articles, and other academic sources related to regional development. The results of the literature review research method are a comprehensive and in-depth understanding of the regional development of Banten Province in the context of development. From the analysis of various written sources, this article identifies the importance of the regional approach in reducing development disparities, as well as regional development strategies that focus on spatial planning, infrastructure, settlements, and sustainable economic growth in Banten.